Maytime [videorecording (DVD)] - Leonard, Robert Z., 1889-1968; MacDonald, Jeanette, 1903-1965; Eddy, Nelson, 1901-1967 (Distributed by Warner Home Video, 2012)
One of the top-grossing films of 1937, Maytime is the poignant, glorious musical that has long been acknowledged as a supreme masterpiece of its genre. See and hear Jeanette MacDonald and Nelson Eddy at the height of their vocal powers and popularity.